Dynamics of Pollen Release and Stigmatic Exposure in Neotropical Piper Species: A Possible Pattern for the Genus - Valentin-Silva, Adriano [UNESP] (2018)
Premise of research.Dichogamy is a common feature in early-divergent angiosperms, as in Piper, and is related to the effectiveness of pollination. To better understand the sexual reproduction in Piper species, we determined whether there is a pattern of pollen release and stigmatic exposure in Neotropical species of this genus, independent of flower sexuality and the number of stamens and carpels.Methodology.We studied 16 Neotropical Piper species, which have flowers with different numbers of stamens and carpels. We analyzed the floral events, in the field and in the laboratory, from bud to senescent flowers.Pivotal results.Twelve species had only bisexual flowers, and four species had bisexual plus staminate flowers. The bisexual flowers of all the analyzed species showed incomplete protogyny: the pistillate phase of flowers lasted from 2 to 7 d, and the bisexual phase lasted from 1 to 9 d. The stigmas were long-lived (4-16 d), and the stigmatic papillae were exposed sequentially and gradually in a basipetal direction, regardless of the number of carpels in the flower. Anther dehiscence was asynchronous and sequential, occurring in one stamen at a time, regardless of the number of stamens and flower sexuality.Conclusions.The dynamic of floral events (sequential and gradual exposure and senescence of stigmas in a basipetal direction, and asynchronous and sequential pollen release) suggests a pattern for Neotropical Piper species, considering that the analyzed species belong to different clades of the genus. In addition, these characteristics may also represent a pattern for the genus as a whole, as the floral development and morphology of bisexual and unisexual flowers are similar.